Development of an interactive game for the evaluation, prevention, and treatment of incontinence-associated dermatitis - Salomé, Geraldo Magela; Jéssica de Aquino Pereira; Duarte, Catherinne Souza da Cruz (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To develop and validate an educational game for the assessment, prevention, and treatment of IAD. Method: The game "IAD – Incontinence-Associated Dermatitis" is an applied research study with technological production. The process followed three stages: analysis, design, and validation. In the analysis phase, an integrative literature review was conducted to support the game's development, identifying assessment, prevention, and treatment measures for IAD. During the design phase, planning and construction of the didactic content were carried out, including topic selection, text development for each screen, media selection, and interface layout design. The validation phase involved 44 experts, using the Delphi technique and the Content Validity Index (CVI), ensuring a validated educational resource for clinical practice. Results: In the initial assessment, most evaluators rated the game from inadequate to fully adequate, with a CVI ranging from 86.36 to 95.45%. After incorporating improvement suggestions, the game was reassessed and rated between adequate and fully adequate, achieving a CVI of 99.99 to 100.00%. Conclusion: The game "IAD – Incontinence-Associated Dermatitis" was developed as an educational tool based on scientific evidence for the assessment, prevention, and treatment of IAD, with the potential to contribute to clinical practice.